2022
DOI: 10.3389/fendo.2022.824269
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Orlistat on Sterol Metabolism in Obese Patients

Abstract: BackgroundOrlistat, a reversible inhibitor of pancreatic and gastric lipase, is known to have anti-obesity and antioxidant properties. Cholesterol intermediates and metabolites have diverse and important functions in cardiovascular disease. Therefore, we aimed to evaluate the effect of orlistat on sterol metabolism in overweight and obese adults after weight loss during the intervention or weight loss at 12 weeks.MethodsA total of 51 (27 in the control group and 24 in the experimental group), patients with a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…There are currently five FDA-approved medications for the management of obesity [10][11][12]. A sixth drug, lorcaserin, was approved for weight loss but was later withdrawn, after being in clinical use for eight years, due to concerns of increased risk of cancer [11].…”
Section: Fda-approved Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently five FDA-approved medications for the management of obesity [10][11][12]. A sixth drug, lorcaserin, was approved for weight loss but was later withdrawn, after being in clinical use for eight years, due to concerns of increased risk of cancer [11].…”
Section: Fda-approved Medicationsmentioning
confidence: 99%
“…Orlistat is a pancreatic lipase and gastric lipase inhibitor that can lead to a decrease in fat absorption by as much as 30% contributing to weight loss [12,13]. Yu et al found that administration of orlistat in combination with diet or diet and exercise versus diet alone led to a reduction in body mass index, body weight, waist circumference, and levels of total cholesterol and low-density lipoprotein (LDL) cholesterol [14].…”
Section: Orlistatmentioning
confidence: 99%
“…The primary outcome was sterol metabolism, which was assessed by measuring the change in the serum levels of sterols from baseline to 12 weeks, and weight was one of the secondary outcomes. 90 At 12 weeks, the drop in weight was 8.6 (0.8) kg with phentermine and orlistat, compared to 6.9 (0.6) kg with phentermine and placebo (p 0.04). Adverse events were not reported.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, hesperidin and naringin in C. amblycarpa peel may have a potential to reduce plasma lipids, and play an important role as antioxidants. 22 Orlistat inhibits fat absorption from triglyceride hydrolysis by inhibiting lipase 24 , which reduces and…”
Section: Table 1 Admet Analysis Of C Amblycarpa Active Compounds and ...mentioning
confidence: 99%